Diagnosis of Metal Hypersensitivity in Total Knee Arthroplasty: A Case Report - Schoon, Janosch; Ort, Melanie J.; Huesker, Katrin; Geissler, Sven; Rakow, Anastasia (Frontiers in Immunology, 2019)
Delayed type hypersensitivity (DTH) reactions are considered infrequent complications in arthroplasty, but have been recognized to be associated with devastating morbidity and substantial decrease in quality of life of affected patients. Chronic inflammation of artificial joints and associated loss of peri-implant bone often require revision surgery. Methods for the diagnosis of implant-related DTH are available but clinically infrequently considered to the full extent. Sequential diagnostics based on exclusion of septic complications, local and systemic metal level determination, lymphocyte transformation testing (LTT), and local T cell subset analysis are required for an unequivocal DTH diagnosis. Here, we report on a patient with a history of chronic rheumatoid arthritis and an unfavorable outcome of unilateral knee arthroplasty. This case illustrates pitfalls and difficulties in the course of recurrent inflammation following joint replacement. In the early course, suspicion of low-grade bacterial infection led to three two-stage revisions. Afterwards, the joint was proven to be sterile. However, metal level quantification revealed release of especially cobalt and chromium from the joint, LTT indicated persisting cobalt and nickel sensitization and subset analysis of T cells from the synovium suggests DTH as a root cause for the inflammatory symptoms. This report aims to recommend the depicted diagnostic algorithm as an adequate tool for future DTH detection. Yet, systemic to local subset ratios for effector memory and regulatory T cells should be derived from sufficient patient numbers to establish it as a diagnostic marker. Moreover, future prospects regarding implant-related DTH diagnostics are discussed. Therapeutic options for the portrayed patient are proposed, considering pharmaceutical, cell-therapeutic and surgical aspects. Patients who experience peri-implant inflammation but do not have obvious mechanical or infectious problems remain a diagnostic challenge and are at high risk of being treated inadequately. Since potentially sensitizing materials are regularly used in arthroplasty, it is essential to detect cases of acute DTH-derived inflammation of an artificial joint at early postoperative stages. This would reduce the severity of inflammation-related long-term consequences for affected patients and may avoid unnecessary revision surgery.